PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII - Zizi Amazane (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematics communication is one of mathematics ability that must be mastered by students’. But, in the fact, students’ mathematic communication of grade 11 SMAN 1 Baso were still low. The learning was still teacher centered. One of solutions was to apply cooperative learning model type Think Pair Share (TPS). Type of research was quasi experiment with Static Group Design. Based on the results of data analysis using t-tests, it is obtained P-value = 0.020 < =0.05, so it is conclude students’ mathematics communication who learn with cooperative model type TPS is better that conventional learning.Keywords – Conventional Learning, CooperativesLearning, Mathematical Communications, Think Pair                        Share.